2014
DOI: 10.4103/0976-3147.127867
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in acute ischemic stroke: Experience from a tertiary care centre in India

Abstract: The management of acute ischemic stroke has undergone a sea of change with the introduction of intravenous thrombolysis (IVT). Current guidelines state that the window period for IVT using rTPA is 4.5 hours. The MERCI, Multi Merci, and Penumbra trials in which patients with acute ischemic stroke were treated using endovascular treatment demonstrated better recanalisation in patients having a large vessel occlusion. However, recently published data from the three large trials IMS 3, Synthesis Expansion, and MR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Data were analysed using INSTAT Graphpad analyser (graphpad.com/scientific-software/instat/) using Spearman's rank correlation method. P-values < 0.05 were considered significant [13].…”
Section: Discussionmentioning
confidence: 99%
“…Data were analysed using INSTAT Graphpad analyser (graphpad.com/scientific-software/instat/) using Spearman's rank correlation method. P-values < 0.05 were considered significant [13].…”
Section: Discussionmentioning
confidence: 99%
“…Authors showed that patients with acute ischemic stroke and large vessels occlusion with no evidence of cross flow through circle of Willis collaterals benefit more from endovascular treatment in comparison with systemic trombolysis. [ 4 ]…”
mentioning
confidence: 99%
“…This observation was confirmed in the study of Huded and coworkers. [ 4 ] Namely, patients who underwent intravenous thrombolysis with documented large vessel disease, with no cross flow on angiogram (insufficient collateral circulation), had less favorable early and delayed outcome as compared to patients treated with endovascular modalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach led to improve acute stroke management proposing the broad using of reperfusion therapies and recommend acute stroke care in the setting of stroke units. [ 3 4 5 ]…”
mentioning
confidence: 99%